PEMBAHARUAN PENDIDIKAN TINGGI ISLAM PRESPEKTIF PEMIKIRAN Prof. Dr. H. MASYKURI BAKRI, M.Si DI UNIVERSITAS ISLAM MALANG - Muhammad Ashrorul Maulana; Muhammad Fahmi Hidayatullah; Dwi Fitri Wiyono (Vicratina : Jurnal Ilmiah Keagamaan, 2022)
This study discusses the renewal of Islamic higher education from the perspective of Prof. Dr. H. Masykuri Bakri M.Si at the Islamic University of Malang. This research is motivated by the low quality of education in Indonesia when compared to education abroad, especially in Islamic education. This research is a type of qualitative research that uses descriptive qualitative research methods. The method used in this study uses interviews, observation and documentation. Data analysis techniques used to collect data through data reduction, data presentation, and drawing conclusions. The conclusions of this study are: The planning at Unisma is divided into five stages, namely, stage I being the Good University Governence, (2011-2015), stage II Teaching University (2015-2019, stage III Research University (2019-2023), stage IV Entrepreneur University (2023-2019). 2027), stage V World Class University (2027-2031). In its implementation, Unisma has now entered the stage of becoming a Research University. Innovations made by Unisma under the leadership of Prof. Dr. H. Masykuri Bakri, M.Si are making Unisma To get to a world-class campus.